Juridical Analysis of Personal Data Protection in the Digital Era: A Case Study of PDP Law Implementation - Judijanto , Loso (Journal of Scientific Insights, 2025)
This study provides a comprehensive juridical analysis of personal data protection (PDP) laws in the digital era, examining the implementation challenges and effectiveness of data protection frameworks across selected jurisdictions. In today's interconnected digital landscape, the increasing collection, processing, and sharing of personal data have raised significant concerns regarding individual privacy rights. Using qualitative descriptive methodology with a library research approach, this study examines the legal frameworks, implementation strategies, and enforcement mechanisms of PDP laws. The research identifies critical gaps between legislative intent and practical implementation, highlighting jurisdictional disparities in approaches to data protection governance. The findings reveal that effective PDP law implementation requires harmonized regulatory frameworks, enhanced institutional capacity, technological adaptability, and strengthened cross-border cooperation. This study contributes to the existing literature by providing insights into the complex interplay between legal protection mechanisms and rapidly evolving digital technologies, offering recommendations for policymakers, legal practitioners, and stakeholders involved in personal data protection.